Dynamics of Russian-Turkish Relations after the Second Karabakh War: New Priorities of National Interests and Strategies of Struggle in the South Caucasus - Gevorg Harutyunyan; Marut Vardazaryan; Svetlana Jilavyan (Journal of Political Science: Bulletin of Yerevan University)
The article analyzes the dynamics of Russian-Turkish relations after the Second Karabakh War of 2020. Particular attention is paid to the fact that the Second Karabakh War was an important military-political step for Türkiye, since, despite being in a bad economic situation and involved in various regional conflicts, Türkiye still managed to act as a new regional superpower and increase its role in the South Caucasus. The article discusses the aggressive steps that led to the fact that Türkiye, having developed and implemented its strategy, without having the necessary natural resources, having many problems within the country, Türkiye can increase its role on several platforms and even show ambitions to be involved in the global governance system. Türkiye opposed the established international relations at the strategic level, putting forward the point of view ‘the world is bigger than five’. At the regional level, combining soft power with hard power for Azerbaijan, Türkiye violated the existing balance and, as a result, increased its share of presence. This is why Russian-Turkish relations are analyzed in the context of the tactical steps taken by Türkiye, as well as in the context of theories of offensive realism and strategic balancing. The article describes how Türkiye, pursuing a more active policy after 2016, managed to prevent the emergence of anti-Turkish coalitions, balance regional rivals, and, if necessary, enter into allied relations with them. In addition, the work used a political-ideological approach to analyze the ideologies and program goals that determine Türkiye’s regional policy, as well as a resource-actor approach, which analyzes the resource base and the activities of states and non-state actors directly involved in the implementation of the foreign policy of the two countries.